Individual differences in activation of the parental care motivational system assessment, prediction, and implication. [article]. - Buckels, Erin E.; Beall, Alec T.; Hofer, Marlise K.; Lin, Eden Y.
We report on the development, validation, and utility of measure assessing individual differences in activation of the parental care motivational system: the Parental Care and Tenderness (PCAT) questionnaire. Results from 1,608 adults (including parents and nonparents) show that 25-item PCAT measure has high internal consistency, high test-retest reliability, high construct validity, and unique predictive utility. Among parents, it predicted self-child identity overlap and caring child-rearing attitudes; among non-parents, it predicted desire to have children. PCAT scores predicted the intensity of tender emotions aroused by infants, and also predicted the amount of time individuals chose look at infant (but not adult) faces. PCAT scores uniquely predicted additional outcomes in the realm of social perception, including mate preferences, moral judgments, and trait inferences about baby-faced adults. Practical and conceptual implications are discussed. - - (from the authors)